Australian Hot Dry Rock Geothermal Energy Potential and a Possible Test Site in the Hunter Valley - Somerville M; Bocking M; Muray A (The Australasian Institute of Mining and Metallurgy, 1995)
Australia has an extremely large total hot dry rock (HDR) resource above a depth of 5 km, equivalent to 7500 times its present annual energy consumption, of which 80 per cent underlies the Great Artesian Basin. The resources most likely to be exploited first are those residing in homogeneous granitic bodies beneath sedimentary basins containing insulating rocks such as shales and coal measures. In the Sydney Basin south of Muswellbrook, an area of high geothermal gradient corresponds to a gravity low thought to be a buried granite body at a temperature of possibly 250¦C. This locality is suspected to have the ideal geological characteristics for Australia's first hot rock test facility. Australia's high HDR potential is possibly unique in the world, in that the potential sites satisfy four independent, geological conditions, each considered as favourable for the creation of a resource, and for the ease of extracting that resource. They are: ò Higher crustal heat generating capacity than that of normal continental crust. ò Much of the Australian continent is covered by sedimentary basins which contain a high proportion of shales and coal measures that have low thermal conductivities, thus providing an insulating blanket for the heat being generated beneath. ò The sedimentary basins are in many places underlain by large untectonised granitic bodies that are not only a major contributor to heat generation, but also ideally suited to the establishment of HDR reservoirs. ò The crustal shortening stress field that is found in the majority of the Australian continental crust results in a vertical minimum principal stress orientation which should result in the development of favourably oriented horizontal stimulation cells necessary for maximising an HDR resource.